2019
DOI: 10.1021/acs.jproteome.8b00964
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Study of Obesity and Its Treatment with Palmitoylated Prolactin-Releasing Peptide Analog in Spontaneously Hypertensive and Normotensive Rats

Abstract: In this study, the combination of metabolomics and standard biochemical and biometric parameters was used to describe the metabolic effects of diet-induced obesity and its treatment with the novel antiobesity compound palm 11 -PrRP31 (palmitoylated prolactin-releasing peptide) in spontaneously hypertensive rats (SHR) and normotensive Wistar Kyoto rats (WKY). The results showed that SHR on a high-fat (HF) diet were normoglycemic with obesity and hypertension, while WKY on the HF diet were normotensive and obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 81 publications
(186 reference statements)
6
16
0
Order By: Relevance
“…Additionally, in SHRs and normotensive Wistar Kyoto (WKY) rats on a high-fat diet, treatment with palm 11 -PrRP31 lowered body weight and improved biochemical and biometric parameters. Palm 11 -PrRP31 also improved glucose tolerance in WKY rats [90].…”
Section: Prrp In the Regulation Of Food Intake And Energy Expenditurementioning
confidence: 99%
“…Additionally, in SHRs and normotensive Wistar Kyoto (WKY) rats on a high-fat diet, treatment with palm 11 -PrRP31 lowered body weight and improved biochemical and biometric parameters. Palm 11 -PrRP31 also improved glucose tolerance in WKY rats [90].…”
Section: Prrp In the Regulation Of Food Intake And Energy Expenditurementioning
confidence: 99%
“…N-butyrylglycine is an acylglycine [41], which is formed by the conjugation of acyl-CoA esters with glycine [42]. Acylglycines are used as diagnostic markers of inborn errors of metabolism [41], and previous studies have shown that acylglycine levels are sensitive in the urine of spontaneously hypertensive rats on a high-fat diet [42]. In this study, we found that acylglycine content was higher under the mixed feed treatment than fermented feed in RIR hens, but the opposite was true for AUS hens.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that acylglycine content was higher under the mixed feed treatment than fermented feed in RIR hens, but the opposite was true for AUS hens. Since N-butyrylglycine is involved in fatty acid metabolism [42], this may indicate that the combination of breed and feed can affect fatty acid metabolism. Actually, linoleic acid in albumen was significantly altered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The HF diet resulted in significant BW gain, mediated by an increase in body fat and liver weight and an increased level of leptin, as shown in Table 2 (Holubova et al, 2016;Čermáková et al, 2019). Furthermore, the consumption of the HF diet significantly increased intolerance to glucose, determined by an oral glucose tolerance test (OGTT) in both rat strains, with significantly increased fasting blood glucose in Sprague-Dawley rats (Holubova et al, 2016) and increased insulin levels in Wistar Kyoto rats compared to those in the low-fat (LF) diet-fed group.…”
Section: Dio Modelsmentioning
confidence: 99%
“…Cholesterol (CHOL), free fatty acid (FFA) and triacylglycerides (TAG) measured from the plasma. Koletsky rats or spontaneously hypertensive obese rats (SHROB), monosodiumm glutamate (MSG), Non-significant (NS), not-tested (NT), Zucker diabetic fa/fa rats (ZDF), (Maletínská et al, 2015;Holubova et al, 2016;Pražienková et al, 2017;Holubová et al, 2018;Mikulaskova et al, 2018;Čermáková et al, 2019;Korinkova et al, 2020). adiposity (Djazayery, Miller, and Stock 1979) because of a lower metabolic rate rather than elevated food intake (Maletínská et al, 2006).…”
Section: Rodent Models With Leptin Deficiency or Disrupted Leptin Signalingmentioning
confidence: 99%